VOCABULARY JOURNAL STRATEGY: ONE WAY TO HELP STUDENTS’ VOCABULARY - Renata C. G. Vigeleyn Nikijuluw (JURNAL TAHURI, 2020)
the discussion of this article aims to the use of vocabulary journal strategy in teaching vocabulary for the students of junior high school. The topic discussion will cover the general concept of learning vocabulary, principle of teaching vocabulary, teaching vocabulary in junior high school, and teaching vocabulary using vocabulary journal. Basically vocabulary journal is a strategy to invite students for strengthen their word knowledge and internalize meaning for use throughout their lives. It is a great strategy to help students’ vocabulary as naturally. Furthermore, some experts suggest that vocabulary journal can be applied in high school levels with different treatment depend on students’ needs and their English proficiency